Can Environmental Regulation Reduce Labor Costs and Improve Business Performance? Evidence From the Air Quality Index - Chai, Kuang-Cheng; Huang, Yang; Chang, Ke-Chiun; Hu, Wen-Jun (Frontiers in Public Health, 2020)
This study examines selected companies in China from 2012 to 2017 matched with provincial air quality index data and uses ordinary least squares regression to examine the relationship between environmental regulation, air quality, employee compensation, and corporate performance. The study found that, first, environmental regulation has eliminated heavy polluting enterprises and promoted the upgrading of enterprise equipment through the cost increase effect, thereby improving regional air quality. Second, good air quality can increase non-monetary benefits for employees, so that corporate employees' monetary compensation can be kept at a low level. Third, in the aforementioned context, with the significant reduction in employee compensation, corporate performance has increased. This study expands the research on the impact of environmental regulation on corporate behavior and enriches the theoretical literature on employee compensation management. Furthermore, to alleviate the adverse effects of high employee compensation on corporate performance under severe air quality, it provides recommendations moving forward. In addition, this study provides empirical evidence for the development of the concept of “lucid waters and lush mountains are invaluable assets” from the perspective of labor cost.